UPAYA MENINGKATKAN PENGETAHUAN MATERI SURAT AL HUJURAT AYAT 13 DENGAN PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING PADA SISWA - Sodiq, Seto Wicaksono; Ade Akhmad Saputra (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2024)
The aim of this research is: (a) Want to know the increase in knowledge of Surah Al Hujurat Verse 13 in class IV students at SDN 41 Plus Banasin III after implementing the Discovery Learning learning model strategy. This research uses two rounds of action research. Each round consists of four stages, namely: design, activities and observation, reflection, and revision. The target of this research was class IV students at SDN 41 Plus Banyuasin III who had not yet fulfilled their KKTP. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the analysis results, it was found that students' knowledge increased from cycle I to cycle II, namely, cycle I (68.00%) and cycle II (92.00%). The conclusion of this research is that the discovery learning model can have a positive effect on student learning motivation, and this learning model can be used as an alternative PAI learning.